Chronic palmitoylethanolamide administration via slow-release subcutaneous pellets promotes neuroprotection and mitigates neuroinflammation in the Tg2576 mouse model of Alzheimer’s disease - Tortolani, Daniel; Decandia, Davide; Giacovazzo, Giacomo; Scipioni, Lucia; Panuccio, Anna; Ciaramellano, Francesca; Eugelio, Fabiola; Fanti, Federico; Latagliata, Emanuele Claudio; La Barbera, Livia; Cutuli, Debora; Compagnone, Dario; et al. (Frontiers in Cellular Neuroscience, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive and non-cognitive decline associated with neuropathological hallmarks, including neuroinflammation. Palmitoylethanolamide (PEA), an endogenous lipid with anti-inflammatory and neuroprotective properties, has emerged as a promising therapeutic agent in managing AD. This study investigated the therapeutic effects of chronic (6-months) PEA administration via subcutaneous pellet in Tg2576 mice, a validated model of AD. The impact of PEA on amyloid precursor protein (APP) processing, astrocytic activation, microglial reactivity and neuroinflammation, nitrosative stress, dendritic spine density in hippocampal CA1 pyramidal neurons, and cognitive performance was assessed. Chronic PEA treatment of Tg2576 mice increased the expression of the α-secretase ADAM9 and reduced astrogliosis. Furthermore, PEA attenuated microglia reactivity, downregulated pro-inflammatory (CXCL13, MCP-1, GCSF) and upregulated anti-inflammatory (CXC3CL1 and IL-9) cytokine expression. Chronic PEA administration also decreased protein nitrosylation, downregulated calcineurin expression, restored dendritic spine density, and improved cognitive functions. Chronic PEA administration offers a promising therapeutic approach for AD by mitigating neuroinflammation, oxidative stress, and synaptic dysfunction, ultimately leading to cognitive function restoration.